Institutional Innovation Strategies in Raising the Income of A Rice Farming Community: A Study of Duriaasi Village, Wonggeduku District, Konawe Regency, Southeast Sulawesi - Arpai, La Ode (UI Scholars Hub, 2019)
This article focuses on institutional innovations in a farming community by linking the institutional approach in increasing farmers’ income. This article finds that institutional innovation is an important aspect in maintaining the sustainability of wet rice farming in Duriaasi Village. Previous studies, such as Vierimaa (2017), only made an analysis using the organizational political approach, while Michael Straub (2017) only explored the role of the mass media in political economy contestations. In contrast to both, this article uses the Fligstein and McAdam’s approach on Strategic Action Fields (SAF), which has a significant effect on analyzing the income of farming communities. Their income of farmers is influenced by the contestations in the purchasing of farmers’ crops by the bargainer (rice millers) inside and outside of the Village. In the SAF concept, the “native” bargainers hailing from Duriaasi village take place as incumbents, while the bargainers from outside the village are taking the position as challengers. This article is written based on a qualitative research, with data collected through desk research, in-depth interviews and observations from July 2017 to January 2018 in Konawe Regency, Southeast Sulawesi.